Rural African American Families, Thriving And Perseverant: Wabaunsee Township, Wabaunsee County, Kansas—1865-1925 - Rivers, James Jr. (Kansas State University. Dept. of History. Chapman Center for Rural Studies, 2010)
James C. Rivers traces the life of an early African American female homesteader, Dicy Nichols. Buying a modest farm in 1867, Dicy Nichols lived there and raised a family until selling her land in 1883 to the Hart-Enlow Ranch. She stayed on the land as a tenant. The author provides photographs of the original site of her land in northern Wabaunsee County, as well as evidence drawn from land records and local recollections.
Keywords: African American; Wabaunsee County; Homesteaders; Women